Scholastic book of lists - Buckley, James, 1963 (New York, NY : Scholastic, 2003)
A reference book lists of information about world history, United States history, social sudies, geography, climate, math, science, language arts, popular culture, animals and the arts.
Includes index.
Keywords: Handbooks, vade - mecums, etc -- Juvenile literature; Handbooks, manuals, etc